Some aspects of transformational effects of bankruptcy law on legal entity construction - M.V. Teliukina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The legal function of bankruptcy law that influences the legal relations regulated by it so that they change in character, inner organization, and ways of implementation has been studied. It could be called transformational (transforming) effects of bankruptcy law. Special attention has been paid to the transformation of various aspects of construction of a legal entity involved in bankruptcy, including contestation of dealings, reorganization of the legal debtor and self-regulatory organizations of insolvency receivers, bringing the persons controlling the debtor to subsidiary responsibility in the framework of the development of the doctrine of piercing of the corporate veil. It has been emphasized that the standards of bankruptcy law do not create a new branch or institution, but modify the existing institutions for the purposes of bankruptcy law.